Fusarium Wilt Disease Control Using Biological Agents Trichoderma and Mycorrhizaeon Pepper - Baswarsiati, Diding Rachmawatiand (El-Hayah : Jurnal Biologi, 2020)
Fusarium oxysporum is the main fungus disease that can wither plants, especially pepper. The fungus spread through diseased soil or already withered plants and then infect plants from its roots. Doing control by using antagonistic fungi such as Trichoderma sp. and Arbuscularmycorrhizae have been widely performed. Trichoderma sp. is a fungus rich with an antifungal activity that produce metabolites, both volatile and non-volatile. These metabolites produced by Trichoderma can diffuse through the dialysis membrane which capable to slow several pathogens growth. Mycorrhizae creates mutual symbiosis between certain types of fungi with roots, also known as biological agents, capable to control F. oxysporum on pepper and to help antibiotics formation. The study was conducted at Laboratorium Hama dan Penyakit BPTP East Java, starting from January to May 2016. This study used completely randomized design (CRD) with treatment consisted of 16 combined doses of Mycorrhizae and Trichoderma, each repeated 4 times that produce 64 test units. Mycorrhizae dose used is 0.0; 1.0; 2.0 and 4.0 grams per polybag, while the Trichoderma dose used is 0.0; 15.0; 30.0; and 45.0 grams per polybag. Data were statistically analyzed by variance analysis and followed by a BNT test of 0.05. The results showed Mycorrhizae 4 g /polybag and Trichoderma 45 g /polybag application could increase the incubation period of F. Oxysporum fungus, shorten xylem discoloration and then reduce wilted plants percentage. Mycorrhizae application can boost Trichoderma fungus in order to reduce wilt disease found in pepper plants